Akta Sebagai Produk Akhir Notaris Menjadi Objek Dalam Persidangan Pidana Pada Pengadilan Negeri Sleman - Elsi Vita Sari (Officium Notarium, 2021)
This study examines “Deed as the Notary’s Final Product Subjected to a Criminal Trial at the Sleman District Court”. The problems formulation are first, whether the final product of a Notary in the form of a deed can be questioned criminally, and second, how is the judge's consideration of a pure acquittal against a Notary who made the deed that is questioned in the criminal trial at the Sleman District Court. This type of research is normative juridical which is supported by information from sources. The approach used in this research is a statutory, sociological and case approach. The results of this study conclude that, first, the final product of a Notary in the form of a deed can be questioned criminally if the criminal elements in the making of the deed can be proven, (i) a deed made before a Notary (consensus) is used as the basis for committing a crime, (ii) a Notary in the making of the deed before or by a Notary which if measured based on the UUJN is not in accordance with the UUJN and (iii) the actions of the Notary are not in accordance with their authorities. Second, the judge's consideration of the pure acquittal of a notary who made the deed was questioned in the criminal trial at the Sleman District Court because the public prosecutor could not prove the existence of a debt agreement, and the criminal elements charged by the public prosecutor were